KONSTRUKSI TAYANGAN IKLAN LAYANAN MASYARAKAT - Rahmi Shinta, Marlina; Raharjo, Agung; Pane, Ilham Alba; Rafiq, A (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2022)
YouTube is a social media where individuals and organizations interact with each other to share information and entertainment. The public service advertisement belonging to the South Jakarta Regional Tax Office I, “Ask AR Aja” is the object of research by researchers. In this public service advertisement, it is seen that there are other meanings of using Islamic religious symbols, and telling stories (Taaruf) with externalization, objectivation and internalization processes using Robert Entman's framing analysis with a qualitative methodology with a case study approach. Based on text analysis, the results of the study frame the way young men and women who are Muslim make introductions to find a mate without going through the courtship process. The externalization process is highlighted in the framing of the scavenger family's condition, which means less prosperous and nice cars on the road, which shows a prosperous family. This is externalized to unmarried individuals, and there are impressions of the struggle of a Muslim woman (Najwa) who is tough, patient, sincere because she has to sell her wealth to pay tax fines. So that these individuals only see messages about tax obligations that must be complied with and high tax fines for violating applicable tax regulations.